The hundreds: my pace of walking provokes my thinking - Yan, Dave (Journal of poetry therapy, 2025)
This arts-based research showcases how the art of writing poetry can be a tool for minorities to navigate everyday precariousness, invisible marginalization, and status silencing. Situated within the practice of poetry therapy, I use a walking poem, as a unique form of performance autoethnography, to produce my inner speech as situated knowledge across various places. In my thinking of subjectivity and lived experience, this walking poem captures the tangible frustration of human existence across various times. Writing and rewriting a hundred lines of thought gives me aesthetic pleasure, enabling me to express the affective, ethical, and performative dimensions of being, doing, feeling, and knowing as an outsider within this academic space. In the process of poetry-making, I engage the sociological imagination, turning private thought into public issues. This is how the poetic is theoretical and philosophical, born out of a necessity, to articulate the everyday practice of being and living on the margins.